Frequent Updater for Health Monitoring System Using Raspberry Pi - Selvarathi, C; Sujatha, R (International Journal of Engineering and Technology, 2018)
In the advancement of Internet technologies all machineries are inter related. Using the technology improvement, we can make many things in high effective and simple for human life. There are several places of Internet of Things (IOT) is used. Such as smart environment, smart home, smart city, smart parking, agriculture fields and medical fields.. In this paper, monitor patientâ€™s heart rate, body temperature, Respiration rate and body movements using Raspberry Pi . After connecting Internet to the Raspberry Pi board it act as a server.. If these parameters are goes to abnormal, it will automatically sends alert message to the doctor. The data send by Raspberry pi is stored on a server. The detailed information of patients and doctor registered through website on stored on server. The people to check health status with help of sensors and patients to access the website from anywhere. In Wireless Sensor Network for acquire the convenient patientâ€™s physiological signal using Raspberry Pi.Â